The Underwriting Cycle in Thai Fire Insurance Industry - Sukkhawadee, Jarut (2005)
Even though the Asian insurance industry has grown significantly in the past decade, the fluctuation in operating results of insurance companies or the underwriting cycle could be observed in many countries, including Thailand. To the extent that the underwriting cycle generates the fluctuation in operating results, profits and loss ratio in insurance industry, this phenomenon is considered to be a major threat that all insurers need to be aware of and develop some measures to mitigate its adverse effects.